Fish reproductive-energy output increases disproportionately with body size - Barneche, Diego R; Robertson, D Ross; White, Craig R; Marshall, Dustin J (Science (American Association for the Advancement of Science), 2018)
Body size determines total reproductive-energy output. Most theories assume reproductive output is a fixed proportion of size, with respect to mass, but formal macroecological tests are lacking. Management based on that assumption risks underestimating the contribution of larger mothers to replenishment, hindering sustainable harvesting. We test this assumption in marine fishes with a phylogenetically controlled meta-analysis of the intraspecific mass scaling of reproductive-energy output. We show that larger mothers reproduce disproportionately more than smaller mothers in not only fecundity but also total reproductive energy. Our results reset much of the theory on how reproduction scales with size and suggest that larger mothers contribute disproportionately to population replenishment. Global change and overharvesting cause fish sizes to decline; our results provide quantitative estimates of how these declines affect fisheries and ecosystem-level productivity.